MERCANTILE HOUSES AND CHEMISTS. APPROACHES TO THE DEVELOPMENT OF THE MEDICAL MARKETPLACE IN URBAN CHILE, 1860-1910 - Correa Gómez, María José (Revista de Historia Social y de las Mentalidades, 2015)
This article presents the Chilean medical  marketplace from the late nineteenth and  early twentieth centuries. Firstly, it examines  the relationship between medicalization and  commerce. Secondly, it shows some features  of the urban medical marketplace through  the international trade, the retail trade and the  celebration of industrial production. It analyses  the growth of the medical market and the  diversification of therapeutics objects, and related  them to the medicalization and urbanization  processes of Chilean society.
Keywords: Medical market; Chemists; Medicalization; Urban Chile